The Impact of Social Media and Infection Perception on the Intentions of Recreational Vehicle Tours: An Extended Model of Goal-Directed Behavior - Chao Zeng; Zihan Yang; Yufan Zhai; Li Yu (Behavioral Sciences)
Despite the rapid expansion of China’s RV (recreational vehicle) tourism industry, research on RV tourist behavior remains limited. This study develops an extended model of goal-directed behavior (EMGB) that more comprehensively explains the formation of tourists’ intentions to engage in RV tourism. The EMGB incorporates critical factors, including the perception of infection (PI), social media influence (SM), infrastructure perception (IP), and perceived advantages of drive tourism (PAD), into the original goal-directed behavior model (MGB). Results from a survey involving 545 RV tourists reveal that the EMGB achieves a satisfactory fit with the data and explains a larger proportion of variance in behavioral intentions. Notably, all variables within the original MGB remain significant predictors of both desire and intention. Furthermore, this study identifies factors such as Time and Economy capability, age, and region as significant moderators of the decision-making process for RV tourists. These findings offer valuable insights to marketers and governmental bodies, empowering them to make more reasonable decisions and devise strategies that cater to the diverse needs and preferences of RV tourists in the future.